PENGARUH KONDISI PERAWATAN PADA KEKUATAN DAN STRUKTUR MIKRO BETON MEMADAT SENDIRI DENGAN VOLUME ABU TERBANG TINGGI - Sondakh, Chichilya S.P.; Manalip, H; Wallah, S. (JURNAL ILMIAH MEDIA ENGINEERING, 2016)
Abstract In the process of normal concrete casting is often to experience constraints due to the distance between the reinforcement is too dense, so it can resulting segregation. Therefore the last few years started to develop Self Compacting Concrete (SCC). SCC is a concrete that is able to solidify themselves with fairly high of slump. In contrast to normal concrete, the composition of cement that needed in the mix design of SCC more than the normal concrete’s. This is also often used as research to find an additives for cement replacement which is appropriate to the nature and characteristics of the cement itself. Fly ash is a waste remnants of coal combustion, an inorganic oxide material that have forming properties such as cement and high water binding capacity. So that the fly ash become a potential material to replace cement in high volume (more than 50%). To obtain the desired strength of concrete there are several factors that must be considered, one of which is the concrete curing. So the researchers conducted a study that aims to observe the effect of curing to the strength and microstructure of High Volume Fly Ash Self Compacting Concrete. Mix design of concrete used with the following composition (1) The volume of coarse aggregate approximately 50% of the volume of solid material, in this study use 40%; (2) The volume of fine aggregate approximately 40% of the volume of mortar, in this study use 48%. (3) water cementitious ratio is 0.72. (4) superplasticizer 2.5%. The volume of fly ash are 0%, 50%, 60% and 70%. Curing is done with 4 ways: Elevated Temperature in the oven for 24 hours in a temperature of 90 ° C and 60 ° C, immersion curing, and without curing. The results showed that the slump flow values increase along with the amount of volume replacement of cement with fly ash. In 60% and 70% of fly ash volume were qualified of self compacting concrete is over 65 cm. The maximum average compressive strength is found at 50% fly ash by mass is on without curing (17.30 MPa). Based on the results of SEM and EDS, It discovery that the higher temperature of treatment indicated a reduction of calcium and silica. So that the reduced of the elements calcium and silica showed reduced the major compounds builder of concrete strength.Keywords: Curing, Compressive Strength, Microstructure, High Volume Fly Ash-Self Compacting Concrete